The Modulatory Role of MicroRNA-873 in the Progression of KRAS-Driven Cancers - Hamada A. Mokhlis; Recep Bayraktar; Nashwa N. Kabil; Ayse Caner; Nermin Kahraman; Cristian Rodriguez-Aguayo; Erika P. Zambalde; Jianting Sheng; Kübra Karagoz; Pinar Kanlikilicer; Abdel Aziz H. Abdel Aziz; Tamer M. Abdelghany; et al. (Molecular Therapy: Nucleic Acids, 2019)
KRAS is one of the most frequently mutated proto-oncogenes in pancreatic ductal adenocarcinoma (PDAC) and aberrantly activated in triple-negative breast cancer (TNBC). A profound role of microRNAs (miRNAs) in the pathogenesis of human cancer is being uncovered, including in cancer therapy. Using in silico prediction algorithms, we identified miR-873 as a potential regulator of KRAS, and we investigated its role in PDAC and TNBC. We found that reduced miR-873 expression is associated with shorter patient survival in both cancers. miR-873 expression is significantly repressed in PDAC and TNBC cell lines and inversely correlated with KRAS levels. We demonstrate that miR-873 directly bound to the 3′ UTR of KRAS mRNA and suppressed its expression. Notably, restoring miR-873 expression induced apoptosis; recapitulated the effects of KRAS inhibition on cell proliferation, colony formation, and invasion; and suppressed the activity of ERK and PI3K/AKT, while overexpression of KRAS rescued the effects mediated by miR-873. Moreover, in vivo delivery of miR-873 nanoparticles inhibited KRAS expression and tumor growth in PDAC and TNBC tumor models. In conclusion, we provide the first evidence that miR-873 acts as a tumor suppressor by targeting KRAS and that miR-873-based gene therapy may be a therapeutic strategy in PDAC and TNBC. Keywords: KRAS, oncogene, non-coding RNA, microRNA, ncRNA, miR-873, proliferation, invasion, gene regulation, tumorigenesis, gene silencing, therapy, nanoparticles, pancreatic cancer, liposomes, breast cancer, triple-negative breast cancer